Relasi Hafalan al-Mufradāt atas Keterampilan Berbicara - Azizah, Siti Fatimatul; Sholihah, Rizki Amalia; Wijayanti, Lisma Meilia (Study Program of Arabic Language Teaching, 2021)
The ability to memorize vocabulary which is a person's effort to be able to do something to memorize vocabulary as much as possible. This memorization ability will affect a person's ability to speak Arabic. The level of language development starts from screaming, sporadic babbling, systematic babbling evidenced through imitation and speech. This type of research is quantitative. The purpose of this study was to determine the ability to memorize vocabulary and Arabic speaking skills of KMI’s student Arrisalah Islamic Boarding School Ponorogo. The selection of this research design always refers to the hypothesis which will later enter the resistance test. This study used a limited population that was heterogeneous because the population was less than 50 people. This study used test, documentation, and observation techniques in the data collection. The data analysis technique of this research used the product-moment correlation technique. Meanwhile, to analyze the results of the study the normality test, linearity test, and paired sample t-test were used. The results of this study indicate that there is a significant relationship between the ability to memorize mufradat and Arabic language skills. This is evidenced by the results of the value of Sig. (2-tailed) 0.000 <0.05.